Separation of ethanol–water mixture by flowsheet with distillation columns at different pressures. - S. L. Nazansky; A. V. Solokhin; V. S. Timofeev (Тонкие химические технологии)
By numerical simulation methods the possibility of separation of ethanol–water azeotropic mixture by means of a distillation unit, including columns at different pressures was investigated.